Soot Blowing Operation Optimization Using PSO Method by Studying Behaviour of Operating Parameter in Sub Critical Coal Fired Power Plant - Sundaram T.; Ismail F.B.; Gurusingam P. (EDP Sciences, 2023)
Boilers; Coal; Coal byproducts; Coal combustion; Coal fueled furnaces; Dust; Energy efficiency; Furnaces; Heat transfer; Natural gasoline plants; Particle swarm optimization (PSO); Soot; Boiler efficiency; Coal-fired power plant; Electrical power generation; Heat transfer rate; Maintenance cost; Operating parameters; Operation optimization; Visual inspection; Fossil fuel power plants